Analysis Of Quality Improvement And Quality Cost Reduction In The 5S Tempeh Production Process At Sirajussaadah Limo Islamic Boarding School Depok - Heni Nastiti; Jenji Gunaedi Argo (SEAN Institute, 2024)
Increasingly tight business competition encourages entrepreneurs to always give the best to consumers such as maintaining product quality. Quality is a factor that can improve the competitiveness of a product. With the improvement of quality, the cost of production will be more minor to reduce waste. Product failure occurs due to several factors: raw materials, machinery, equipment, people and the environment. To maintain the quality of the products produced and by the market's needs, it is necessary to conduct quality control (Quality Control) on the process activities carried out. This study aims to find out the quality control of tempe SS products in Pondok Pesantren (Ponpres) Limo Depok using the Kaizen PDCA and move 5S (Seiri, Seiton, Seiso, Seiketsu dan Shitsuke)